The effect of HR practices and organizational engagement on turnover intention: a study in a selected region in Malaysia - Juhdi, Nurita; Hansaram, Ram Milah@Simranpreet Kaur; Pa'wan, Fatimah; Othman, Noor Akmar (2011)
The major objective of the study was to assess the effect of HR practices on organizational engagement and turnover intention. Four hundred and fifty seven employees in a region in Malaysia participated in the survey. HR practices examined were career management, compensation, person-job fit, job control and performance appraisal. All these variables were found positively related to organizational engagement. Career management was indicated as the strongest predictor for organizational engagement and performance appraisal being the weakest. Organizational engagement was found as a partial mediator between HR practices and turnover intention. The findings imply that any initiative to affect turnover intention, organizational engagement must be addressed first.